Analytical model to determine optimal production lots considering several productive and logistics factors (2014)
The current economic crisis has led companies worldwide to pursue costs reductions in order to remain productive. To support this effort we propose an analytical model to establish the optimal lot size based on the celebrated EOQ (Economic Order Quantity) model. The value of this model is that –in order to provide solutions closer to the actual optimal– it includes several costs factors, many of them never before considered. Of particular interest are the incorporation of two characteristics of the model, the "Logistical index" first published in Revista Dyna Colombia, 179 [1], and the possibility of working with variable production times, features never included in a model of this type before. Also, to facilitate the implementation of this model several in companies, including SMEs, two simplifications and a solved problem are showed.